69.3k views
1 vote
Hello please help me with this I need an answer immediately thank you so much see image

Hello please help me with this I need an answer immediately thank you so much see-example-1
User GarouDan
by
5.7k points

1 Answer

4 votes

We know that:


PA = PB = 15

Using the Pythagorean theorem in the right triangle on the right we have:


CP ^ 2 = CB ^ 2-PB ^ 2

Then, again using the Pythagorean theorem in the right triangle on the left we have:


CA ^ 2 = CP ^ 2 + PB ^ 2

Substituting values:


CA ^ 2 = (CB ^ 2-PB ^ 2) + PB ^ 2

Rewriting the expression:


CA ^ 2 = CB ^ 2


CA = CB


CA = 15

Answer:

The value of CA is given by:


CA = 15

User Vikas Ojha
by
5.5k points